2020
DOI: 10.5194/acp-2020-315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global-scale distribution of ozone in the remote troposphere from ATom and HIPPO airborne field missions

Abstract: Abstract. Ozone is a key constituent of the troposphere where it drives photochemical processes, impacts air quality, and acts as a climate forcer. Large-scale in situ observations of ozone commensurate with the grid resolution of current Earth system models are necessary to validate model outputs and satellite retrievals. In this paper, we examine measurements from the Atmospheric Tomography (ATom, 4 deployments in 2016–2018) and the HIAPER Pole-to-Pole Observations (HIPPO; 5 deployments in 2009–2011) experim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(90 reference statements)
2
1
0
Order By: Relevance
“…After the seasonal variance is remove, only 13% of the total variance remains (i.e., 18.5 ppb 2 ), indicating that the spatial variability and zonally similar seasonal cycles dominate the variance of monthly mean baseline ozone at northern midlatitudes. The northern midlatitude zonal similarity found in this work is consistent with a recent analysis of the ozone observations from the remote troposphere collected during the global HIPPO and ATom airborne field missions (Bourgeois et al, 2020). This study found that the ozone distribution was similar in the extra tropics over the Atlantic and Pacific Oceans in both the Southern and Northern Hemispheres.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After the seasonal variance is remove, only 13% of the total variance remains (i.e., 18.5 ppb 2 ), indicating that the spatial variability and zonally similar seasonal cycles dominate the variance of monthly mean baseline ozone at northern midlatitudes. The northern midlatitude zonal similarity found in this work is consistent with a recent analysis of the ozone observations from the remote troposphere collected during the global HIPPO and ATom airborne field missions (Bourgeois et al, 2020). This study found that the ozone distribution was similar in the extra tropics over the Atlantic and Pacific Oceans in both the Southern and Northern Hemispheres.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that the ozone distribution was similar in the extra tropics over the Atlantic and Pacific Oceans in both the Southern and Northern Hemispheres. Consistent with the hypothesis guiding this work, Bourgeois et al (2020) attributed the similarity to the zonal circulation of baseline ozone.…”
Section: Discussionsupporting
confidence: 82%
“…The DC-8 FIREX-AQ payload included the NOAA Nitrogen Oxides and Ozone (NOyO3) instrument, a well-established O3 225 measurement using the chemiluminescence technique (Ryerson et al, 2000;Bourgeois et al, 2020). ROZE operated simultaneously with the NOyO3 instrument during several flights.…”
Section: Validation Against Chemiluminescencementioning
confidence: 99%